Governing Urban Tourism: Strategies to Balance Regulation, Sustainability, and Resident Well-Being - Saucedo-Calzada, Rafael; Dias, Álvaro; Almeida-García, Fernando; Cortés-Macías, Rafael (Taylor & Francis, 2025)
Urban tourism presents a governance paradox: it drives economic growth yet often heightens resident discomfort and social tensions under overcrowding. While prior research has examined regulation, sustainability planning, and economic impacts, their combined influence on residents’ perceptions remains underexplored. This study employs a dual-method design—Partial Least Squares Structural Equation Modeling (PLS-SEM) and fuzzy-set Qualitative Comparative Analysis (fsQCA)—to identify governance configurations shaping resident attitudes in saturated contexts. A stratified survey of 450 Málaga residents shows that regulation and sustainable planning follow an inverted U-shaped pattern: discomfort rises when governance is either weak or overly rigid, and decreases at moderate levels. Perceived equitable economic benefits reduce discomfort, while fsQCA highlights multiple pathways linked to both high and low discomfort, underscoring that no single strategy is universally effective. These findings emphasize adaptive, context- sensitive governance integrating resident perspectives and equity, offering an evidence-based framework for socially sustainable policies in high-pressure urban destinations.
https://openpolicyfinder.jisc.ac.uk/id/publication/18987
Keywords: Turismo urbano - Aspectos económicos; Política turística; Turismo - Aspectos sociales; Geografía humana; Urban tourism governance; Overtourism; Tourism policy; Sustainable planning; Residents perceptions; fsQCA